THU0155 Customised construction of devices as integration of occupational therapy intervention in rheumatology by 3d printing technology and co-design: further development and verification of long-term effectiveness. (12th June 2018) - Sandri, G.; Gherardini, F.; Anastasio, C.; Bettelli, V.; Bottini, A.; Mascia, M.T.
Abstract : Background: In our previous study 1 we have analysed the potentiality to create customised personalised aids through the 3D printing technique for patients with chronic physically and psycho-socially progressively disabling rheumatic diseases. It has been shown that the active involvement of the patient in the aid prototyping process through co-design sessions allows a greater acceptance of the aid itself in daily activities. Objectives: To confirm the effectiveness of custom co-designed aids made with 3D printing technique. To check long-term patient's satisfaction in their daily use. To demonstrate that a client-centred intervention leads to aids greater acceptance, reduces social stigma and improves self-esteem. Methods: 9 patients affected by long term rheumatoid arthritis were enrolled overall. They expressed their specific needs regarding the aid devices and therefore subsequent meetings were organised that have allowed us to produce and deliver customised objects. Tools: Autodesk Fusion360 and Dassault Systemes SolidWorks for object modelling; Ultimaker Care for slicing; 3D printing DeltaWASP 20 40 Following a co-design approach, 6 aid devices were customised: hand grip holder for chalk, tablespoon, aid to open the moka coffee machine (2 different models), cans opener, zip puller. For the collection of the design features the product analysis of the USERfit tool was used. The psycho-social impact assessment of the assistance by PIADS (Psychosocial Impact of Assistive Devices Scale) and the patient's satisfaction by QUEST (Quebec User Evaluation of Satisfaction with Technical Aids, scale 1–5) were analysed after 1 week and after 1 year Results: After 1 year all co-designed aids are still in use and the patients' satisfaction remains unchanged. The psychosocial assessment of delivered aid devices, collected through PIADS (– scale −3+3), showed an overall positive outcome (mean competence +1.92; adaptability:+1.590; self-esteem:+1.70). The assessment of patient satisfaction through QUEST, was good (scale 1–5: satisfaction aid: 4.65; service satisfaction: 4.9). There are no significant changes between scores after 1 week and 1 year except for a reduction in the self-esteem score (p=0.006) Conclusions: This work shows that an interactive co-design, made possible by 3D printing, allows patients with long-established strategies in the activities of daily life to change habits, satisfactorily. The decrease of self-esteem scores could be probably due to a lower patient's emotional involvement with respect to an object that has become a regular part of his life. Reference: [1] Sandri G, Bottini A, Franchi F, et al. THU0705 Experimental use of 3D printing technology for the construction of devices as integration of occupational therapy intervention with rheumatoid arthritis patients (RA). Annals of the Rheumatic Diseases2017;76:474. Disclosure of Interest: None declared